A prospective cohort study to refine and validate the Panic Screening Score for identifying panic attacks associated with unexplained chest pain in the emergency department. Issue 10 (25th October 2013) - Foldes-Busque, Guillaume; Denis, Isabelle; Poitras, Julien; Fleet, Richard P; Archambault, Patrick; Dionne, Clermont E
Abstract : Introduction: Panic-like anxiety (panic attacks with or without panic disorder), a highly treatable condition, is the most prevalent condition associated with unexplained chest pain in the emergency department. Panic-like anxiety may be responsible for a significant portion of the negative consequences of unexplained chest pain, such as functional limitations and chronicity. However, more than 92% of panic-like anxiety cases remain undiagnosed at the time of discharge from the emergency department. The 4-item Panic Screening Score (PSS) questionnaire was derived in order to increase the identification of panic-like anxiety in emergency department patients with unexplained chest pain. Methods and analysis: The goals of this prospective cohort study were to (1) refine the PSS; (2) validate the revised version of the PSS; (3) measure the reliability of the revised version of the PSS and (4) assess the acceptability of the instrument among emergency physicians. Eligible and consenting patients will be administered the PSS in a large emergency department. Patients will be contacted by phone for administration of the criterion standard for panic attacks as well as by a standardised interview to collect information for other predictors of panic attacks. Multivariate analysis will be used to refine the PSS. The new version will be prospectively validated in an independent sample and inter-rater agreement will be assessed in 10% of cases. The screening instrument acceptability will be assessed with the Ottawa Acceptability of Decision Rules Instrument . Ethics and dissemination: This study protocol has been reviewed and approved by the Alphonse-Desjardins research ethics committee. The results of the study will be presented in scientific conferences and published in peer-reviewed scientific journals. Further dissemination via workshops and a dedicated website is planned.